Pembelajaran Berdiferensiasi dalam Upaya Memaksimalkan Potensi Peserta Didik - Al Hafiz Rasya Ramadhan; M Juniyansah; Safina Desfianti; Sani Safitri; Syarifuddin Syarifuddin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Differentiated learning is an approach that adapts the learning process to the needs, interests, and abilities of each student so that they can learn optimally according to their own style and pace. This approach aims to create a more meaningful learning experience, allowing each student to develop their potential to the fullest, and building an inclusive and equitable environment where all learners have the same opportunity to thrive. With a more dynamic learning atmosphere, students feel valued and supported in their academic journey. To implement differentiated learning effectively, teachers must have the skills to identify individual student needs, design flexible learning strategies, and create teaching materials that can be accessed and understood by all students. With this approach, the effectiveness of learning increases, while encouraging students to be more active, confident, and independent in exploring knowledge.